The Relationship Between Neonatal Nurses' Attitudes, Evidence-Based Practice Leadership Evidence Based Practice Work Environment, and the Involvement of Parents on in Family Centered Care Practices: A Cross-Sectional Study - Selvinaz Albayrak; Zehra Kan Öntürk; Emine Türkmen; Nilgün Göktepe; Sabiha Çağlayan (Association of Nurse Managers, 2023)
Aim:  This study aimed to: a) examine the effects of neonatal intensive care nurses' attitudes towards evidence-based practices and perceptions of evidence-based practices leadership and work environment on attitudes towards parental participation, and (b) determine the effects of such attitudes and perceptions of nurses on parental involvement in neonatal intensive care unit family center care activities. Method:   This cross-sectional study was conducted with 218 neonatal intensive care nurses in Turkey using an online questionnaire. The data were collected using the demographic questionnaire, the Evidence-based Practices Work Environment Scale, the Evidence-based Practices Leadership Scale, the Attitude Towards Evidence-Based Nursing Questionnaire, the Parental Participation Attitude Scale, and the number of parental involvement direct care activities. Data were analyzed with descriptive statistics, Pearson correlation, and multiple regression analysis (backward). Results:  Nurses' attitudes towards parental participation were affected by evidence-based nursing attitudes (R2=0.35, Durbin-Watson=2.078, p<0.001). The number of parent-delivered interventions related to family center care activities in the neonatal intensive care unit was affected by the evidence-based practices environment and completion of neonatal intensive care unit certification (R2=0.11, Durbin-Watson=1.972, p<0.001). Conclusions:  Nurses' attitudes towards parental involvement affects by their own evidence-based practices knowledge and awareness. The establishment of an evidence-based practices work environment at the organizational level and the provision of special training for nurses increased parent-delivered interventions.